Manajemen Pengelolaan Aset Wakaf Sosial Produktif: Pelatihan Profesionalitas Nadzir Wakaf Lembaga Keagamaan dan Rumah Ibadah - Anam, Faris Khoirul; Ikhsan, M. Alifudin; Hanafi, Yusuf; Fauzi, Moh. Fery (Faculty of Cultural Studies, Universitas Brawijaya, 2025)
This community service program aims to improve the competence of nazhir in managing productive social waqf assets in Malang. The target audience includes 36 participants from 12 endowment assets around the campus of Malang State University and Wagir Subdistrict. The implementation methods include endowment asset management training, endowment jurisprudence socialization, and technical assistance using a multi-method approach, including interactive presentations, experiential learning, and on-site mentoring. Key findings indicate a significant improvement in nazhir understanding and skills regarding productive waqf development. However, a KAP (Knowledge, Attitude, Practice) survey revealed knowledge gaps in key aspects of waqf jurisprudence and its practical implementation. While attitudes toward modernizing waqf management are positive, challenges remain in implementing sustainable training and due diligence. Going forward, there is a need for intensive education programs on productive waqf, the development of a nazhir incentive system, and the optimization of performance monitoring. The establishment of a communication forum among nazhirs and multi-stakeholder collaboration in developing a comprehensive training curriculum are recommended to build a professional nazhir ecosystem, thereby optimizing the potential of waqf for the welfare of society.